Prosecuting child sexual abuse in rural Kentucky: Factors influencing case acceptance by prosecuting attorneys - Moore, Darin K. (American journal of criminal justice, 1998)
This study examined the relationship between felony prosecutors’ discretion and the legal and social factors present in cases of child sexual abuse. Prosecuting attorneys from 20 rural circuits in Kentucky were targeted for semistructured interviews in order to determine what influences them to accept or not accept a case for prosecution. Findings show a relationship between rural Kentucky prosecutors’ decision to accept a case and the availability of physical evidence, victims’ age and competence, potential trauma inflicted upon the victim, and the situation in which the allegation of sexual abuse originated. The relationship between prosecutors’ discretion and various factors is discussed regarding the impact on other criminal justice officials in their pursuit to combat child sexual abuse in Kentucky and in other rural communities as well.